Determinan yang Mempengaruhi Kepuasan Hunian dan "Word Of Mouth" di Villa Ana Residence Samarinda - Kokom Komariyah (OECONOMICUS Journal of Economics, 2018)
This study discusses the Determinan yang mempengaruhi kepuasan hunian dan "Word of Mouth" di Villa Ana Residence Samarinda. More specifically, the objectives of this study were 1) to determine and analyze the effect of the product on the Company's customer satisfaction at Villa Ana Residence Samarinda, 2) To identify and analyze the effect of the price to the consumer on Villa Ana Housing Residence Samarinda, 3) To identify and analyze the influence of service developers to consumer satisfaction at Villa Ana Housing Residence Samarinda, 4) identify and analyze the effect of customer satisfaction on WOM (Word of Mouth) in Company Villa Ana Residence Samarinda. Results showed that: 1) The product positive and significant effect on customer satisfaction in the Villa Ana Residence Samarinda, 2) Prices are not positive and significant effect on customer satisfaction in the Villa Ana Residence Samarinda, 3) Developer Services and significan positive effect on customer satisfaction in Villa Ana Residence Samarinda, 4) positive customer satisfaction and significantly towards WOM (Word of Mouth) in Villa Ana Residence Samarinda. The Results of this study provide practical implications that the Villa Ana Residence particularly emphasized that the indicator products in the diversity of products, product quality, design, size and Warranty. Services confidence indicator developer or Reliability, Responsiveness or Responsibility, Confidence or Assurance, Empaty and Tangible. The practical implication of this research is that it can be used as a reference by the Party Villa Ana Residence Management to improve determinants or factors affecting residential satisfaction and "Word of Mouth" at Villa Ana Residence Samarinda based on 24 indicators.